GIT&S and PGIS for developing countries - Kyem, Peter (Technical Centre for Agricultural and Rural Cooperation, 2005)
Peter Kyem explains that although both conventional GIT&S and participatory GIS approaches can contribute to natural resource planning and management in developing countries, PGIS offers specific added value.